Ruang Representasional untuk Pencurahan Kasih Sayang pada Pusat Perbelanjaan (Studi Kasus: Festival Citylink, Bandung) - Hanan Marta Lina; Agus Suharjono Ekomadyo (RUAS, 2021)
To fulfill the desire for social existence, even during the pandemic, people still visit shopping malls, one of which is Festival Citylink. This study aims to examine the representational space aspect of the places at Festival Citylink where shopping activities are a representation of social existence which in shopping mall theory is referred to as "efforts to convey affection". This research is qualitative-descriptive with data collection methods through 2-stages interviews, observation, photo documentation, and literature studies. The sample was selected using a non-random/purposive sampling method. Data collected were analyzed using Lefebvre's representational space aspect with a framework using Miller's Making Love in Supermarket theory. The results showed that love making occurred through shopping activities with the implementation of shopping type arranged, free shopping, discussion, and knowing each other, also through giving treats and savings. This love making is accommodated by srepresentational spaces, these are supermarkets, food courts, and department stores. The spaces are produced with various adjustments to signage, furniture, materials, lighting, layout, space proportions, thermal comfort, themes, and facilities.